Perfil de citocinas em pacientes com espondilite anquilosante - Rabelo, Cristina Ferreira (2016)
Introduction.Ankylosing spondylitis (AS) is a chronic disease featuring axial changes, peripheral arthritis and systemic involvement. Proinflamammatory cytokines are probably involved in AS pathogenesis. The relationship of circulating cytokines with instruments of AS evaluation is an open field. We herein compared serum levels of cytokines in AS patients and healthy controls, and searched for correlations of cytokines with indexes of disease activity and quality of life. Methods. In this cross-sectional study, 32 AS patients and 32 age-and-sex matched controls were evaluated. BASDAI, BASFI, BASMI, ASDAS-CRP, MASES, ASQol and PGA were measured in AS patients. The soluble cytokines IL-6, IL-8, IL-1, IL-10, TNF-, IL-12p70 and IL-17 were quantified by flow cytometry. IL-23 concentrations were obtained in an ELISA. Results. Overall, AS patients were predominantly males (59.4%) and Caucasians (96.9%). Mean age was 46.9±10.7 years. HLA B27 was present in 70% of cases. Concentrations of IL-6, IL-8, IL-10 and TNF- were higher in AS cases than controls. Mean concentration of IL-6 correlated with the BASMI, an index of axial mobility (rs= 0.354, p=0.047). Anti-TNF intake (present in 21 patients, 65.6%) associated with a high BASMI (p=0.042) and lower quality of life as measured by the ASQol (p=0.009). Conclusions. A proinflammatory cytokine profile predominated in AS patients, but interestingly the IL-10 concentrations were also elevated, pointing to an attempt of a suppressive control of inflammation. A defined correlation of serum IL-6 with the BASMI suggests a role for this cytokine in axial disease. Anti-TNF users had more axial activity and lower quality of life.